1978
DOI: 10.1111/j.1467-6494.1978.tb00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Veridicality of cognitive mapping of stressor effects: Sex differences1

Abstract: In order to examine the veracity of judgment-questionnaire data regarding the effects of confronting a stressor in various contexts, judgments based on the imagined consequences of these encounters were scaled for both male and female subjects using individual-differences multidimensional scaling analyses. A parallel experiment was then carried out where a second group of subjects were directly exposed to the spectrum of stressor-context combinations previously judged. The two experiments substantially differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…With regard to indices whose sensitivity to stress response was more apparent than that of other indices, it is noteworthy that measures of cardiac reactivity significantly distinguished anxiety proneness groups in line with earlier findings of the relative sensitivity of this index for males (Hodges & Spielberger, 1966;Lefave & Neufeld, 1980). Cardiac reactivity contrasts the physiological index of frontalis muscle tension in that, among females, the latter measure has been shown to be relatively more sensitive to the effects of stressing stimulation Neufeld, 1978; and to anxiety proneness differences in these effects (Neufeld, 1976). As expected on the basis of earlier findings for physical danger anxiety proneness among male and mixed-sex samples (Lefave & Neufeld, 1980;Neufeld, 1975), skin conductance was similarly sensitive to stimulus properties (graded task difficulty) for each anxiety proneness group.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…With regard to indices whose sensitivity to stress response was more apparent than that of other indices, it is noteworthy that measures of cardiac reactivity significantly distinguished anxiety proneness groups in line with earlier findings of the relative sensitivity of this index for males (Hodges & Spielberger, 1966;Lefave & Neufeld, 1980). Cardiac reactivity contrasts the physiological index of frontalis muscle tension in that, among females, the latter measure has been shown to be relatively more sensitive to the effects of stressing stimulation Neufeld, 1978; and to anxiety proneness differences in these effects (Neufeld, 1976). As expected on the basis of earlier findings for physical danger anxiety proneness among male and mixed-sex samples (Lefave & Neufeld, 1980;Neufeld, 1975), skin conductance was similarly sensitive to stimulus properties (graded task difficulty) for each anxiety proneness group.…”
Section: Discussionsupporting
confidence: 80%
“…The present results resemble those of other studies directed to other sources of individual differences in stress response, specifically sex differences. 6 Male-female differences in stress response have been consistently obtained over several studies (Hare, Wood, Britain, & Frazelle, 1971;Kimmel & Hill, 1961;Neufeld, 1978; 7 despite similar male-female configurations from unidimensional and multidimensional scaling analyses of cognitive mapping of stressing situations (Neufeld, 1978;. On the other hand, when scaled appraisal was devoted specifically to the effects of direct stress encounter, systematic sex differences accordant with differences in actual responses were obtained (Hodges & Felling, 1970;.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Only males served as subjects because of documented sex differences in stress response (e.g. Neufeld, 1978;Neufeld & Davidson, 1974), possibly impinging on cognitive functioning as measured here. Practical constraints made infeasible subject division on the basis of gender, additional to that of psychometrically designated stress susceptibility.…”
Section: Subjectsmentioning
confidence: 99%
“…This suicidal behavior may be a reflection of their greater tendency to respond to environmental Stressors with higher cognitive threat and intropunitiveness. Neufeld (9) found that female undergraduate students responded more than their male counterparts on several psychophysiological indices when confronted with actual Stressors.…”
mentioning
confidence: 99%